Mendorong Otonomi Kampus dan Kesempatan Belajar Mahasiswa - Fazri Diolizuardi; Chintya Ayu Nurwidya; Masduki Asbari; Fathir Muhammad (Journal of Information Systems and Management (JISMA), 2024)
This research aims to explore the implementation of the "Freedom of Learning" policy initiated by the Ministry of Education and Culture of the Republic of Indonesia. The main focus of this research is to identify the objectives of the "Free Campus" policy and how its implementation supports campus autonomy and expands student learning opportunities. This research uses a descriptive qualitative method by taking note-taking because the data source was obtained by listening to oral narratives from the Indonesian Ministry of Education and Culture's Youtube channel entitled "Siniar #PojokDikbud: Encouraging Campus Autonomy and Expanding Student Learning Opportunities". The research results show that the Independent Campus program has great potential to help students develop skills and knowledge that are relevant to the world of work, so that they can be ready to face the changes and dynamics that occur in society and industry under any conditions.